Trade unions of Russia in the system of social partnership: legal regulation, problems and prospects of development - G. N. Obukhova (Правоприменение, 2023)
The subject. Proclaiming the ideas of partnership and solidarity, the state designates a completely new development focused on socio-economic relations in Russia, involving new principles of interaction between society, business and the state. The revision of the status of subjects of social partnership will be aimed at further development of the system of guarantees of human and civil rights and freedoms. Purpose of the study. The purpose of this work is a comprehensive analysis of the trade union as a subject of social partnership based on the study, analysis and generalization of the scientific base, current legislation and practice of its application. Effective protection of the rights and legitimate interests of employees is possible only if there is an effective mechanism of implementation of trade union control over their compliance. Therefore, it seems that in the near future the share of public control over compliance with labor legislation and labor protection should increase. Methodology. In the process of achieving the goal and solving the tasks set, the general scientific dialectical methods of cognition, as well as logical, historical, comparative legal and formal legal methods were used. Structural and systemic methods are also the basis of the study. The conclusions of the work are based on dialectical unity and the struggle of opposites. The main results. In the process of scientific research, it can be concluded that a society should be able to exercise public control over the observance of human rights in this society. During the reforms, trade unions lost the right to legislative initiative at the federal level, the rights to state supervision of compliance with labor legislation and the state of labor protection, and consideration of individual labor disputes. At the same time, trade unions have re-ceived a number of new rights, for example, to participate in the resolution of collective labor disputes, in collective bargaining, to conclude social partnership agreements, etc.Despite the declared principle of independence of trade unions from the state, as a result, it is impossible to create and legalize the legal status of the trade union movement without a state regulator. Therefore, the independence of any legal entity is, in principle, relative. Nevertheless, associations of employees are provided with a sufficient amount of corporate independence, which actually ensures their national and individual characteristics. Conclusions. Trade unions are an important element of civil society. Without increasing their role, it is impossible to achieve harmony in social and labor relations. In this regard, the question of the new status of trade unions in Russia should be raised. This conclusion is justified by the fact that free and independent trade unions are the guarantors of social justice and security. Consequently, the use of the market mechanism by the population depends on whether it is possible to regulate the labor market within the framework of law and policy. Moreover, the labor market improves the status of employees in relation to employers only with strong trade unions.